2001
DOI: 10.1051/0004-6361:20010058
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic shear analysis in 50 uncorrelated VLT fields. Implications for $\Omega_0$, $\sigma_8$

Abstract: Based on observations obtained at the Very Large Telescope UT1 (ANTU) which is operated by the European Southern Observatory (program 63.O-0039A).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
132
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(140 citation statements)
references
References 17 publications
8
132
0
Order By: Relevance
“…where J n is a Bessel function of order n. This shear variance has been used in many weak lensing analysis to constrain cosmological parameters (Maoli et al 2001;Hoekstra et al 2006;Fu et al 2008). -The shear two-point correlation function, which is currently the most widely used statistic because it is easy to implement and can be estimated even in cases of complex geometry.…”
Section: Two-point Statisticsmentioning
confidence: 99%
See 2 more Smart Citations
“…where J n is a Bessel function of order n. This shear variance has been used in many weak lensing analysis to constrain cosmological parameters (Maoli et al 2001;Hoekstra et al 2006;Fu et al 2008). -The shear two-point correlation function, which is currently the most widely used statistic because it is easy to implement and can be estimated even in cases of complex geometry.…”
Section: Two-point Statisticsmentioning
confidence: 99%
“…However, when deriving joint constraints, a degeneracy exists between σ 8 and Ω m (see e.g., Maoli et al 2001;Hoekstra et al 2002;Semboloni et al 2006). This degeneracy between σ 8 and Ω m is typical of cosmic shear measurements that use only two-point statistics.…”
Section: Two-point Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…shear-selected dark matter haloes were reported in the literature (see Erben et al 2000;Umetsu & Futamase 2000;Maoli et al 2001;Wittman et al 2001Wittman et al , 2002Miralles et al 2002;Miyazaki et al 2002;Dahle et al 2003;Schirmer et al 2003, for example). About half of these objects have optical counterparts, the nature of the others remains unclear.…”
Section: Introductionmentioning
confidence: 98%
“…The first detections of cosmic shear on wide-field imaging data (Bacon et al 2000(Bacon et al , 2002Kaiser et al 2000;van Waerbeke et al 2000van Waerbeke et al , 2001van Waerbeke et al , 2002Wittman et al 2000;Maoli et al 2001;Rhodes et al 2001;Hämmerle et al 2002;Hoekstra et al 2002;Refregier et al 2002) has demonstrated the feasibility of this new window of observational cosmology, and yielded already the first constraints on cosmological parameters, most noticibly the normalization σ 8 of the dark matter power spectrum, but also on the matter density parameter Ω m Hoekstra et al 2002).…”
Section: Introductionmentioning
confidence: 99%